2016
DOI: 10.1002/cbic.201600197
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Norbornene‐Modified Mannosamine Derivatives for Metabolic Glycoengineering

Abstract: Metabolic glycoengineering (MGE) allows the introduction of unnaturally modified carbohydrates into cellular glycans and their visualization through bioorthogonal ligation. Alkenes, for example, have been used as reporters that can react through inverse‐electron‐demand Diels–Alder cycloaddition with tetrazines. Earlier, norbornenes were shown to be suitable dienophiles; however, they had not previously been applied for MGE. We synthesized two norbornene‐modified mannosamine derivatives that differ in the stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 68 publications
0
37
0
1
Order By: Relevance
“…This was attributed to low incorporation of the bulky norbornene structure. 205 206 and zebrafish 207 using bioorthogonal sugar derivatives. In one example, Bertozzi et al developed a bioorthogonal approach for systemic imaging of glycans by metabolically incorporating a BCN-functionalized sialic acid (BCNSia 1) at various development stages of Zebrafish, following by IEDDA labelling.…”
Section: Metabolically Incorporation For Glycan Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to low incorporation of the bulky norbornene structure. 205 206 and zebrafish 207 using bioorthogonal sugar derivatives. In one example, Bertozzi et al developed a bioorthogonal approach for systemic imaging of glycans by metabolically incorporating a BCN-functionalized sialic acid (BCNSia 1) at various development stages of Zebrafish, following by IEDDA labelling.…”
Section: Metabolically Incorporation For Glycan Modificationmentioning
confidence: 99%
“…Due to the orthogonality between IEDDA and azide-alkyne cycloaddition, most IEDDA-sugars may be used for dual labelling with Ac4GlcNAz. 106,107,117,199,200,205 In one example, Wittmann et al simultaneous incorporated cyclopropene and azide handles in cell surfaces and performed orthogonal dual labelling with a Tz dye and DIBO-488. 107 Despite the fast kinetics of IEDDA compared to SPAAC, longer incubation of Tz probes (3 hours for the norbornene sugar and 6 hours for terminal alkenes) was necessary for efficient staining due to low incorporation efficiency.…”
Section: Metabolically Incorporation For Glycan Modificationmentioning
confidence: 99%
“…The same authors recently reported a series of norbornene‐tagged mannosamine derivatives suitable for metabolic engineering of glycan structures. They also demonstrated the dual‐colour labelling potential of these derivatives in combination with SPAAC chemistry …”
Section: Fluorescent Glycan Labelling Through Metabolic Engineeringmentioning
confidence: 96%
“…We found that 43 % of all released sialic acids bear the acrylamide functionality (Figures S2 and S3); this demonstrates the high acceptance of this small reporter group by the enzymes. In comparison, mannosamine derivatives modified with a bulky norbornene were found to be incorporated with an efficiency of only 1 % . These findings also show that the acrylamide group is stable during metabolization and not attacked by thiols in a Michael‐type addition.…”
Section: Methodsmentioning
confidence: 99%